Effect of microsphere size on the drug release and experimental characterization of an electrospun naringin‐loaded microsphere/sucrose acetate isobutyrate (SAIB) depot. (30th January 2020) - Zhang, Dan; Song, Jinlin; Almassri, Huthayfa N.S.; Ma, Yihui; Zhang, Ting; Cheng, Yuting; Wu, Xiaohong
Abstract : The aims of this study were to prepare different sizes of electrospun naringin‐loaded microspheres (Ng‐ms) and investigate the effects of the particle size of these microspheres on drug release from naringin‐loaded microsphere/sucrose acetate isobutyrate (Ng‐m‐SAIB) hybrid depots to develop an improved drug delivery system for tissue engineering. Different sizes of microspheres were produced using electrospray methods by controlling electrospinning parameters. The Ng‐m‐SAIB depots were prepared by dispersing Ng‐ms in SAIB depots. The morphology and size distributions of the electrospun Ng‐ms were characterized by polarizing microscopy and scanning electron microscopy (SEM). To better understand the release behavior of Ng‐m‐SAIB, the porosity of SAIB depots was measured. Consequently, both small (2.51 ± 0.191 μm) and large (5.03 ± 0.172 μm) microspheres exhibited smooth surfaces and good monodispersity. The initial and long‐term drug release rates of the large microspheres were lower than those of small microspheres. On the first day after 2.5‐μm and 5‐μm Ng‐m‐SAIB depots were produced, the burst release reduced dramatically from 68.79% to 3.30% and from 63.20% to 0.00%, respectively. After 92 days of release, the drug release rate of 5‐μm Ng‐m‐SAIB was still lower than that of 2.5‐μm Ng‐m‐SAIB, with values of 58.54% and 63.93%, respectively. These results demonstrate that drug release from Ng‐m‐SAIB depots can be tailored solely by varying the size of the microspheres and that good drug release behavior occurred.